Overexpression of β‐expansin gene GmEXPB2 improves phosphorus efficiency in soybean. Issue 2 (11th July 2013) - Zhou, Jia; Xie, Jianna; Liao, Hong; Wang, Xiurong
<x xml:space="preserve">Abstract</x> Soybean (Glycine max) is an important oil crop in agricultural production, but low phosphorus (P) availability limits soybean growth and production. Expansin is a family of plant cell wall proteins and involved in a variety of physiological processes, including cell division and enlargement, root growth and leaf development. To test the potential effects of expansins on crop production, we have developed soybean transgenic plants overexpressing a soybean β‐expansin gene GmEXPB2, which was significantly induced by phosphate (Pi) starvation. The results indicated that constitutive overexpression of GmEXPB2 promoted leaf expansion, sequentially stimulated root growth and consequently resulted in improved P efficiency in the transgenic plants under P‐limited conditions in hydroponics. In particular, when tested in calcareous (CS) and acid soils (AS), the two GmEXPB2 transgenic soybean lines showed above 25 and 40% increases in plant dry weight and P content, respectively to wild‐type plants in low‐P CS, but not in AS. To our knowledge, this is the first report in which improvement of P efficiency could be achieved through constitutive overexpression of an endogenous EXPB gene in soybean. These findings suggest that genetic modification of root and leaf traits might be a suitable strategy for improving crop production in low‐P soils.